Linguistic Demography of Himachal Pradesh - Negi, Harvinder Kumar (Nepalese Linguistics, 2022)
Himachal Pradesh is characterized by high ethno-linguistic heterogeneity and small language communities that face risk of disappearing due to changes in demography, lack of documentation and institutional policies (Negi, 2016). This article verifies the language varieties in Himachal Pradesh along with domains of use, institutional policies and the vitality of languages, relying on previous studies by Devy & Tobdan (2016), Negi (2012;16), Tobdan (2018), and field study conducted between 2017 and 2019 to corroborate the varieties.